Audit Committee, Independent Commissioners, Firm Size, and Intellectual Capital on The Financial Performance of State-Owned Enterprises - Andriani, Chintia; Pratiwi, Devica; Theresia Olivia; Albert Sebastian (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to explain the effect of audit committees, independent commissioners, company size, and intellectual capital on financial performance proxied by return on assets (ROA) in State-Owned Enterprises (BUMN) companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The population used is all BUMN companies listed on the IDX in 2020-2022. Sampling was selected using purposive sampling method, in order to produce samples that match the research criteria. The research sample amounted to 15 companies with a period of 3 years to 45 total samples. The data collection technique was carried out using the documentation method in the form of annual reports for the 2020-2022 period obtained from the IDX and the company's official website. The data collected was analyzed with multiple linear regression using SPSS 26. The results of this study indicate that the audit committee variable has a significant value of 0.000 and a t value of 5.360, the independent commissioner variable has a significant value of 0.670 and a t value of 0.430, the company size variable has a significant value of 0.000 and a t value of -7.375, and the intellectual capital variable has a significant value of 0.022 and a t value of -2.375, so that the only accepted hypothesis is H1, namely, the audit committee affects financial performance and other hypotheses are rejected. The audit committee, independent commissioners, company size, and intellectual capital have an influence of 61.1%, while the rest with a value of 38.9% can be influenced by other variables that are not in this research model. Audit committee variables affect financial performance, independent commissioners have no effect on financial performance, while company size and intellectual capital have a negative effect on financial performance. Future researchers are expected to add other variables besides the variables in this study and can use other more accurate measurement methods.